Fate of External Carotid Artery Following Carotid Artery Stenting for Internal Carotid Artery near Occlusion - Dorota Łyko-Morawska; Michał Serafin; Julia Szostek; Magdalena Mąka; Iga Kania; Wacław Kuczmik (Biomedicines, 2025)
Background: The external carotid artery (ECA) plays a vital role in facial perfusion and acts as a collateral pathway for cerebral blood flow during internal carotid artery (ICA) stenosis. In cases of carotid near-occlusion (CNO), characterized by severe ICA stenosis with hemodynamic changes, carotid artery stenting (CAS) is rising as a potential new treatment. During CAS, the stent is deployed in ICA, covering the ECA orifice. Therefore, this study aims to evaluate the effects of CAS on ECA. Materials and Methods: This retrospective study included 159 patients diagnosed with CNO and treated with CAS between February 2018 and May 2023. Preoperative and postoperative ECA diameters were measured using angiography. Data on patient demographics, procedural details, and outcomes were analyzed. Results: The median preoperative ECA diameter was 4.34 mm, decreasing to 3.40 mm post-CAS (p < 0.001). ECA narrowing occurred in 76.39% of patients, while 4.17% experienced occlusion. A larger preoperative ECA diameter was predictive of narrowing (odds ratio (OR) = 1.35, p = 0.02) and protective against occlusion (OR = 0.1, p < 0.001). Weak correlations between ICA and ECA diameter changes were observed, indicating procedural influences on ECA dynamics. Conclusions: CAS for CNO significantly reduces ECA diameter, with a subset of patients developing occlusion. The preoperative ECA diameter is a key predictor of postoperative changes. These findings emphasize the need for further research on CAS-related ECA hemodynamic alterations to optimize patient outcomes and minimize complications.